Fibroblast Activation Protein-α as a Target in the Bench-to-Bedside Diagnosis and Treatment of Tumors: A Narrative Review - Xin, Lei; Gao, Jinfang; Zheng, Ziliang; Chen, Yiyou; Lv, Shuxin; Zhao, Zhikai; Yu, Chunhai; Yang, Xiaotang; Zhang, Ruiping (Frontiers in Oncology, 2021)
Fibroblast activation protein-α (FAP) is a type II integral serine protease that is specifically expressed by activated fibroblasts. Cancer-associated fibroblasts (CAFs) in the tumor stroma have abundant and stable expression of FAP, which plays an important role in promoting tumor growth, invasion, metastasis, and immunosuppression. For example, in women with a high incidence of breast cancer, CAFs account for 50–70% of the cells in the tumor’s microenvironment. CAF overexpression of FAP promotes tumor development and metastasis by influencing extracellular matrix remodeling, intracellular signaling, angiogenesis, epithelial-to-mesenchymal transition, and immunosuppression. This review covers the basic biological characteristics of FAP and its applications in the diagnosis and treatment of various cancers. Furthermore, we review the emerging basic and clinical research data regarding the use of nanomaterials that target FAP.